Nursing Students’ Learning Through ACLS Simulation: A Scoping Review - Windy Zega; Yakobus Siswadi (Faculty of Nursing, Universitas Pelita Harapan, 2025)
Simulation learning is widely used in nursing education to improve clinical competence and emergency preparedness. In Advanced Cardiac Life Support (ACLS), simulation provides nursing students with realistic scenarios to enhance decision-making, teamwork, and technical competencies. This scoping review aimed to explore: (1) the learning experiences of nursing students participating in ACLS simulation and (2) the barriers to its implementation in nursing education. Although numerous studies support the effectiveness of simulation, there remains limited synthesis on how nursing students learn through ACLS simulations, the challenges involved, and the outcomes achieved. These methods used a scoping review that followed the Joanna Briggs Institute guidelines and the PRISMA flowchart. English-language articles published between 2015 and 2025 were retrieved from three electronic databases. Five studies met the inclusion criteria and were critically appraised using the Quality Assessment with Diverse Studies (QuADS) tool. A total of five studies met the inclusion criteria and were included in the review. Three overarching themes emerged: (1) learning processes encompassing cognitive, psychomotor, and non-technical skills development; (2) student experiences characterized by increased confidence and emotional growth; and (3) barriers such as emotional distress, limited team communication, and technological constraints. These findings show that ACLS simulations provide valuable experiential learning but require supportive facilitation. The Conclusion ACLS simulation significantly supports the learning experience of nursing students, improving clinical judgment, skills, and confidence. However, barriers, including emotional strain, communication challenges, and limited institutional resources, must be addressed to ensure effective implementation and sustained learning outcomes. Recommendation is that educators should promote emotional safety, structured debriefing, and ensure equitable access to simulation resources to maximize the learning outcome.